Pengaruh Inovasi Dan Kolaborasi Terhadap Keunggulan Bersaing Pada UMKM Industri Makanan Kota Sukabumi - Kholipah Al Mugni; Deni Muhammad Danial; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the description of innovation and collaboration as well as competitive advantage in the Food Industry UMKM in Sukabumi City. In addition, this study also aims to determine the effect of innovation and collaboration on competitive advantage in the Food Industry UMKM in Sukabumi City. Researchers used descriptive and casual associative research methods with a quantitative approach because they distributed questionnaires to 41 MSMEs in the Food Industry in Sukbumi City. The data analysis technique that the researcher uses in this research is validity test, reliability test, normality test, multiple linear regression, multiple correlation coefficient, coefficient of determination, and hypothesis testing T test and F test. The results show that innovation and collaboration variables have a strong relationship. a strong variable with competitive advantage with a value of 0.755. The results of hypothesis testing show that the innovation and collaboration variables have a positive and significant influence on the competitive advantage variable in the Food Industry UMKM in Sukabumi City. Keywords : Innovation, Collaboration, Competitive advantage